The Role of Ex Combatants Party Against The Advocacy of Political Representation of Women In The Post-Conflict in Aceh, Indonesia - Satris, Rezki (Universitas Muhammadiyah Yogyakarta, 2021)
This study discusses the role of ex-combatant parties in advocating post-conflict women by using the Aceh Party case study. Aceh Party is one of the parties that transformed the struggle movement from the armed movement into a political party movement through general elections. The ex-combatant party was formed by post-conflict combatants after peace negotiations. The ex-combatant party which later became the case study material in this study was the ex-combatant party (Aceh Party) in Aceh. The presence of ex-combatant parties as part of the democratization process has a different reception towards the equality discourse of women in the participation and representation of public spaces, especially representation in politics. The Aceh Party has a tendency for women only as a formality to fulfill a 30 percent quota, without involving women seriously in political matters. This certainly can be seen how the party programs tend to be gender biased. The purpose of this study is to look at the phenomenon of the presence of post-conflict ex-combatant parties as part of the democratization process in providing advocacy for women. Through this research with a qualitative approach both sourced from primary and secondary data by tracing various literature, documents, and other supporting materials.